Correlation between Serum Malondialdehyde levels and prevalence of cardiovascular disease in Haemodialysis treated patients - Rehman, Sadia; Mahboob, Tabassum; Kamali, Muhammad Farhan (Journal of the Pakistan Medical Association, 2022)
Objectives: To investigate the role of serum malondialdehyde as a diagnostic biomarker of free radical production and cardiovascular disease in patients treated with maintenance haemodialysis. Method: The case-control study was conducted in the Department of Biochemistry, Basic Medical Sciences Institute (BMSI) of the Jinnah Postgraduate Medical Centre (JPMC), Karachi, and the JPMC Nephrology ward from January 12, 2018, to January 15, 2019, and comprised patients receiving haemodialysis as the cases and healthy controls. Blood samples were obtained from all the subjects for checking the level of serum malondialdehyde. Doppler ultrasonography was employed to detect the intima media thickness ratio of the common carotid artery of all the subjects. Data ws analysed using SPSS 23. Results: Of the 90 subjects, 45(50%) each were cases and controls. There were significant differences in mean values related to age, body mass index and blood pressure between the groups. A statistically significant rise was seen in serum malondialdehyde and carotid artery intima media thickness ratio in the cases compared to the controls (p<0.05). Conclusion: Serum malondialdehyde was found to be significantly raised in haemodialysis patients compared to the healthy controls. Key Words: Malondialdehyde, Haemodialysis, Cardiovascular disease, Oxidative stress, Free radicals.